Macrofauna bentônica de praias arenosas intermediarias nas proximidades da foz do Rio Doce - Silva, Emanuely Ezidio da (2023)
The hydrodynamics acting along the beach system result from the interaction of abiotic factors such as waves, beach face slope, and sediment grain size. These factors together determine the morphodynamic degree of the beach. The complexity of these environments increases with the proximity of river mouths due to the influence of sediment transport and discharge from rivers. Many studies have shown direct correlations between benthic macrofauna and the physical characteristics of the beach, with macrofauna being determined by morphodynamics. However, studies that address the association of benthic fauna with the mobility of topographic profiles and morphodynamic states are still lacking. Therefore, the objective of this study was to analyze the structure of the benthic community in response to variations in morphodynamic conditions on exposed sandy beaches north of the mouth of the Rio Doce, ES. Six sandy beaches that had already been monitored by PMBA north of the Rio Doce were selected for this study, with eight sampling campaigns from Sep/2018 to Jan/2022. Sediment samples were collected for physical and biological characteristics at each beach, and topographic profiles and morphodynamic characteristics of the beaches were also surveyed. The beaches exhibited variations in Dean's omega, which reflects the morphodynamic state, as well as variations in beach face slope and mean grain size. Variations in Dean's omega and slope were also found between sampling campaigns at two of the beaches. The beaches closer to the mouth of the Rio Doce showed high profile mobility larger slopes and mean grain sizes. The beaches further north from the mouth had lower profile mobility and smaller beach face slopes. Species richness and organism density varied among different mobility levels, with higher values observed in beaches with high-profile mobility. Correlations were also found between fauna and changes in morphodynamic states. In beaches with moderate profile mobility, species richness increased as the beaches became more dissipative. In beaches with high-profile mobility, density increased as the beaches became more reflective. Although the community structure differed among mobility levels, the specific composition of the macrofauna was nearly the same, with oligochaete worms, polychaetes like Saccocirrus pussicus and Hesionura cf. variodentata, Hemipodia simplex, and the isopod Excirolana brazieliensis predominating. Differences were primarily due to variations in species abundance at each mobility level. The similarity in community composition among different mobility levels and morphodynamic states confirms the tolerance of these organisms to abiotic variations. The proximity of the Rio Doce mouth was the determining factor in profile mobility and the morphodynamic and morphological conditions of the beaches, as well as in the structure of the macrofauna. Proximity to beaches with high-profile mobility ensured high densities of opportunistic and tolerant organisms. Fauna responded more to changes in morphodynamic states than to profile mobility. Variation in morphodynamic states appears to directly control species richness on exposed intermediate beaches, while density appears to have been controlled by organic enrichment in sediments near the river mouth.